Предмет: Алгебра,
автор: gerasimovgleb224
(m+n)(m²-mn+n²)-(m+n)³
Please
Help мне
Ответы
Автор ответа:
2
Ответ:
(см. объяснение)
Объяснение:
(m+n)(m²-mn+n²)-(m+n)³=m³+n³-(m+n)³=m³+n³-(m³+3m²n+3mn²+n³)=-3mn(m+n)
Автор ответа:
0
Ответ:
m+n
(m+n)(m²-mn+n²)-(m+n)³=(m+n)(m²-mn+n²)-(m+n)(m²-mn+n²)=(m+n)(m²-mn+n²-m²+mn-n²)=m+n.
Во второй скобке идет сокращение подобных.
Похожие вопросы
Предмет: Другие предметы,
автор: vini98
Предмет: Українська мова,
автор: Ldanylo
Предмет: Другие предметы,
автор: DAHANAGO
Предмет: Биология,
автор: Unka778